Profil Penggunaan Obat Antihipertensi Pada Pasien Lanjut Usia Yang Dirawat Inap RS Akademik UGM - Titami, Arina; Wiedyaningsih, Chairun; Pratama, I Dewa Putu (Majalah Farmaseutik, 2023)
Hypertension is a common disease that is simply defined as a persistent increase in arterial blood pressure. Elderly is correlated with increased blood pressure, which increases the risk of heart disease, stroke, and kidney disease. Intensive treatment of hypertension can significantly reduce the risk of heart and cerebral vascular disease, including target organ damage. This study is an observational study with a retrospective cohort design. The subjects in this study were elderly patients with a diagnosis of hypertension who were hospitalized at the Gadjah Mada University Academic Hospital (RSA UGM) Yogyakarta in the period January 1, 2021–December 31, 2021. The data in this study were sourced from the medical records of the UGM RSA. Data analysis was carried out descriptively to describe the profile of the use of antihypertensive drugs in elderly patients with a diagnosis of hypertension who were hospitalized. The number of patients in that period was found to be 534 patients and then 120 patients who met the inclusion criteria. The 60-69 years age group was the most patient group (71 patients). The proportion of women was more (73 patients) than men. The highest prevalence of comorbidities was diabetes as many as 29 patients. The highest prevalence of length of stay in hospital (LoS) is 1-5 days as many as 66 patients. In this study, the most common use of antihypertensive drugs in elderly patients with hypertension who were treated at UGM RSA was combination therapy (66 patients). Most patients used single therapy with calcium channel blocker (CCB) antihypertensive drugs, namely amlodipine as many as 24 patients and the most combination therapy was amlodipine and candesartan as many as 20 patients.